Transient Cooling Of A Cylinder In Cross Flow Bounded By An Adiabatic Wall - Saeid, Nafaw H.; Abusahmin, Bashir S. (ASEAN Journal of Chemical Engineering, 2023)
The present study investigates the parameters controlling the cooling process of a cylindrical food in the storage area for a period of time. Transient analysis of the conduction and convection (conjugate) heat transfer from a cylindrical food, or a cylindrical can filled with food is selected for numerical simulations. The cylinder is bounded by an adiabatic wall and the cold air is flowing normal to the cylinder axis (cross flow). The parameters investigated are: Reynolds number, food thermal properties (density, specific heat and thermal conductivity) and the cooling period. The range of the Reynolds number is selected from 50 to 500 to be in laminar flow conditions. Three different materials were selected according their thermal properties. The results are presented to show the cooling process starting from blowing cold air stream on the cylinder for a period of 4 hours. The results show that the food with low thermal inertia is cooled faster than that of high thermal inertia. The present results show also that the cooling process can be shortened by increasing the air velocity and lower its temperature.